Pinworm Infestation Mimicking Crohns' Disease. (11th March 2013) - Johansson, Joel; Ignatova, Simone; Ekstedt, Mattias
Abstract : We here report a case of a young man who presented to his general practitioner with diarrhea. Inflammatory bowel disease was suspected and a colonoscopy showed aphthous lesions suggestive of Crohns' disease but biopsies revealed eggs of Enterobius vermicularis. When treated for this parasite, his symptoms were alleviated and a followup colonoscopy revealed a normal colon and distal ileum. Enterobius vermicularis is the most common parasite worldwide and has been attributed with many different presentations and pathologies. It is therefore necessary to maintain vigilance, even in high-income countries, in order to diagnose patients with one of the many atypical presentations of pinworms.